Principal Leadership in Developing Adaptive Educational Management Culture in Elementary Schools - Agusalim; Isaac John Ibanga; Maria Ulfa; Muhammad Yusnan; Waode Riniati; Hijrawatil Aswat; Yeni Setiani (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to analyze how principal leadership contributes to the development of an adaptive educational management culture in elementary schools, particularly in responding to policy changes, learning needs, and the dynamics of school governance. Methods: This study employed a qualitative case study design involving three elementary schools: SD Negeri 2 Baubau, SD Negeri 2 Palatiga, and SD Negeri Palatiga. This study employed a qualitative case study design involving three elementary schools. Fifteen informants, consisting of three principals, nine teachers, and three educational staff members, were selected purposively. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing/verification. Findings: The findings reveal that adaptive educational management culture is developed through five interconnected mechanisms: translating the school vision into daily work practices, strengthening participatory communication, involving teachers in decision-making and program implementation, promoting context-based program flexibility, and using reflective evaluation as a space for organizational learning. Research Implications: The study implies that principals need to strengthen collaborative governance, reflective supervision, teacher participation, and context-sensitive decision-making to build schools that are more responsive to institutional and pedagogical change. Originality: This study offers a contextual model of adaptive educational management culture by positioning principal leadership as a cultural and relational practice rather than merely an administrative function. lies in the placement of the principal's leadership as a cultural practice that constructs an adaptive management culture through social relations and organizational learning, not just an administrative function.